The Relationship Between Factors Affecting Property Development and Housing Affordability in Abuja, Nigeria - Gombwer Nenrot Wuyokwe (International Journal of Scientific Research and Innovative Studies, 2022)
Notwithstanding their best efforts, the Nigerian government and the private sector on real estate have not been successful in providing housing in the context of Abuja as the federal capital the low middle and even high-income earners have complained about access to affordable housing. There are several factors influencing property development that is linked to the non-availability of this lack of housing affordability. This study focuses on the assessments of the relationship between factors affecting property development and housing affordability in Abuja, Nigeria, the study employed the quantitative research design, where 121 sets of a questionnaire were distributed after design and validations, and 77 sets of the questionnaire were retrieved and used for the analysis where correlational statistical analysis was used to find the relationship it was revealed from the result of the study that there a strong relationship between the factors affecting the property development and the housing affordability in Abuja, Nigeria of r=58.7% and it was concluded that cost of labor, building material cost, access to land, cost of development, mortgage interest rate, are more having linkage with the housing affordability in the study area. The public and the private sector have shown an effort toward housing provision in Abuja but, there are still a need government and the other private sectors to tackle these factors that threaten housing affordability. These factors have a relationship with the housing affordability determination.